2019
DOI: 10.1101/770586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic integration of behavioural and endocrine components of the stress response

Abstract: 22The stress response is a product of selection for an integrated suite of behavioural and 23 physiological traits that facilitate coping with acute stressors. As such, genetic variation 24 in the stress response is expected to reflect genetic variation in, and genetic covariation 25 among, its behavioural and physiological components. Such genetic integration among 26 stress response components has yet to be formally demonstrated using multivariate 27 quantitative genetics, despite its profound implications f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 132 publications
(260 reference statements)
0
4
0
Order By: Relevance
“…60%; Gustafsson et al, 2011), and more controlled laboratory (e.g. 28%; Houslay et al, 2019) or wild experimental animal studies (e.g. 40%; Bairos-Novak et al, 2018) in which GC variation was directly manipulated by the observers.…”
Section: Discussionmentioning
confidence: 99%
“…60%; Gustafsson et al, 2011), and more controlled laboratory (e.g. 28%; Houslay et al, 2019) or wild experimental animal studies (e.g. 40%; Bairos-Novak et al, 2018) in which GC variation was directly manipulated by the observers.…”
Section: Discussionmentioning
confidence: 99%
“…In all of our analyses, we modeled corticosterone changes after disturbance as within-individual reaction norms, drawing on the growing literature and methods that have been developed for this type of data from behavioral studies (e.g., Allegue et al, 2017; Hertel et al, 2020). A number of conceptual reviews have suggested that physiological stress responses should be considered as reaction norms (Hau et al, 2016; e.g., Taff and Vitousek, 2016; Wada and Sewall, 2014), but relatively few empirical studies have explicitly taken this approach to date (but see, Fürtbauer et al, 2015; Houslay et al, 2022) and we are not aware of any comparative papers that have modeled corticosterone responses as reaction norms.…”
Section: Methodsmentioning
confidence: 99%
“…There is ample evidence both that thermal flexibility occurs in hormones and that hormones in turn support physiological, behavioral, and morphological traits that likely promote thermoregulation, evading unfavorable conditions, or temperature related changes in behaviors that influence fitness. For example, glucocorticoids mediate changes in behavior, such as foraging, locomotion, and parental care in individuals [38]; although studies showing covariation of flexibility for glucocorticoids and flexibility in behavior at the individual level are rare [but see 74]. Behavioral thermoregulation involves moving to the shade, forgoing foraging [73], reducing chick provisioning in high heat [75,76] or moving to different places [77], among others.…”
Section: Endocrine Flexibility As a Facilitator Of Coping With Changi...mentioning
confidence: 99%